Estudo da redação Enem: questões e perspectivas de uma práxis interdisciplinar e colaborativa - Luiz, Ana Paula Aparecida de Tarso (2018)
My research proposal intends to analyze the quality and social relevance of the Enem Writing produced throughout the school year by high school students, linked to a private school in Uberlândia (MG), in order to analyze if the impasses that make difficult the understanding of the subject, the production of the text and the ability to mobilize socio-cultural repertoire and voices in written production are related to the difficulty of students to meet the competencies II and III required in the matrix of correction of the Enem or if they refer to the difficulty of students to develop the argumentative-argumentative textual type. From this, I investigate whether this student develops the written competence to do the Enem or if the production context that involves the Enem Writing practice favors the students to think beyond this selective process. The specific objectives are: a) to examine the content, the organization of the textual plan and the discursive and sociocultural repertoire manifested in the essays produced in order to critically analyze the text from the perspective of the competences II and III collected in the reference matrix of the proof of writing of the Enem; b) investigate the critical formation and construction of arguments of the research participants; c) find out if the essays produced present a critical position on the theme addressed in the texts supporting the proof; d) analyze whether the mobilization of voices and interdisciplinarity occurs in the text to develop the argumentative course; e) show how the writing class can contribute to the student's critical development beyond Enem. This research is based on the theoretical and methodological assumptions of Discourse Partner Interactionism (ISD), discussed by Bronckart (1999, 2006 and 2008) as well as in the critical reflection on the teaching of the genre Enem Writing from the considerations of Schneuwly and Dolz (2004) . My research option is qualitative research; Thus, for the development of this study, I use the assumptions of Nunan (1992) and André (1995). The corpus is developed from: a) analysis and reading of the Enem Writing produced by the research participants; b) critical evaluation of these texts based on the attendance (or not) of the competencies indicated by the examining bank of the Enem; c) data collection to analyze the difficulties that the students present regarding the domain of the dissertation-argumentative discursive type, the knowledge apprehension and the critical development of the problematic in question in addition to the Enem; e) presentation and analysis of interventions in the writing classes that allow the approach of the genre beyond the Enem, in order to contribute to the development of the criticality of the student. Based on this theoretical basis and critical reflections, I intend to carry out a study that can contribute to the production of the Enem Drafting without limiting it to a single purpose, making possible the development of the student's critical and linguistic formation.